Blockchain-based solutions for agri-food supply chains: a survey. (8th February 2022) - Mirabelli, Giovanni; Solina, Vittorio
In recent years, interest in blockchain technology has grown considerably, due to its multiple properties, such as transparency, immutability, traceability, security. Considering the significant number of recently published contributions about the use of blockchain-based solutions in the agri-food sector, in this paper we aim to collect and catalog them. The main purpose is the identification of research trends and possible barriers to the large-scale spreading of this disruptive technology. Through a well-structured four-step research methodology, we systematically review 48 papers. The main result is that blockchain can be used not only to ensure complete food traceability, but also to protect workers' rights, limit the power of supply chain intermediaries and protect market prices, enable reward mechanisms for the development of sustainable initiatives. However, there are still some open issues that limit its large-scale diffusion: lack of shared standards, limited number of real case studies, resistance by stakeholders, restricted scalability.